LEGAL PROTECTION ON GEOGRAPHICAL INDICATION AS A PART OF INTELLECTUAL PROTECTION RIGHTS - Yessiningrum, Winda Risna (Jurnal IUS, 2015)
Geographical indication is a mark of product that indicates the originality, due to geographical environment including factors of nature, human or combination of both which containing particular characters and qualities within a product. Those characters and quality are maintained and sustained in certain length of time which will contribute reputation (well known) over the product and may raising its economic value. Based on research result, it may conclude that geographical indication matter is urgency to be legally protected. As it may guarantee the basic rights of the holder and actualized the sense of safety of a product, as it produce naturally or coming from a very specific human idea that cannot be found in another area and owns specific reputation. That it may increase competitiveness of a region and require a better concern from the local government. Geographical indication is a quality indicator where the geographical indication indicates the area of origins of a product to the customers. Keywords: Protection, legal, originality.